TH2.1: Understanding femininities: Implications for women's Participation in Agricultural interventions in central Uganda - Shimali, Fred; Mangheni, Margaret Najjingo; Mwiine, A.A.; Businge, M.; Nakyewa, B.; Nanyonjo, G.; Angudubo, S.; Sanya, L.N.; Asiimwe, E. (Makerere University, 2022)
Research has documented how men's behaviors in patriarchal settings affect women's economic empowerment outcomes, while less attention has been paid to how gender identity constructions around femininities influence these outcomes. We define femininities as gender based roles and expected behaviors of women in a given community and economic empowerment as women's decision-making regarding access and control of productive resources and management of income. This paper presents research on how female and male farmers in rural communities of central Uganda define what it means to be a woman and how those identity constructions influence women's economic empowerment. This qualitative case study is based on focus group discussions conducted with Sasakawa Africa Association intervention farmers (28 women and 25 men) of Kiboga District. Six focus group discussions were conducted, two with men only, women only, and both men and women respectively. Findings reveal co-existence of traditional and progressive femininities, dubbed "unruly" by men and some women. Traditional femininities were depicted as women complying to community values which deter them from financial decision making and owning productive resources. Progressive femininities on the other hand are noncompliant to these community values, and enjoy more economic empowerment. Men valued economically empowered women because they relieve men of financial responsibilities. Incorporating gender transformative approaches in women's economic empowerment interventions could decode traditional femininities and increase women's intrinsic agency within the context of economic empowerment.